(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The article analyses the system of Lithuanian protected territories as well as their types form environment conservation point of view. The system of protected territories of LR includes the following types of areas: 6 state reserves, 1 biosphere reserve, 396 strict reserves, 5 national parks, 30 regional parks, 29 biosphere polygons and 3 recuperation plots. The system of protected territories, the order of establishment, management and the legal basics of protection of protected territories is determined by the law of protected areas of LR that was approved in 1993. The purpose of reserves is to preserve unique landscape complexes, their biota gene pool, to organize scientific research and observation, to promote natural and cultural values. The aims of the establishment of Lithuanian national and regional parks are not only to preserve naturally and culturally valuable landscape but also to support ethno cultural traditions of Lithuanian regions and to provide conditions for recreation. The purpose of strict reserves is to preserve the complexes of natural and cultural heritage or separate landscape elements, plant and animal species, to secure landscape diversity and ecological balance. Live and inanimate natural monuments are preserved naturally for scientific, cultural, educational and aesthetic needs. The purpose of biosphere polygons is to preserve bird species by assuring favorable conditions, to perform the monitoring of protected species, scientific research, etc. The aim of the recuperation plots is to restore natural resources. The system of Lithuanian legal acts allows applying such limitations that are necessary to preserve existing values in every protected territory.